Factors and Outcomes Associated With Venous Thromboembolism Following Bariatric Surgery. Issue 10 (October 2022) - Mabeza, Russyan Mark; Lee, Cory; Verma, Arjun; Park, Mina G.; Darbinian, Khajack; Darbinian, Shushanna; Yetasook, Amy; Benharash, Peyman
Background: The present national study characterized the incidence and factors associated with VTE following bariatric operations and its association with postoperative outcomes and resource use. Methods: Adults (≥ 18 years) undergoing elective sleeve gastrectomy or gastric bypass (laparoscopic and open) were identified in the 2016-2018 Nationwide Readmissions Database. International Classification of Diseases 10th Revision codes for deep venous thrombosis and/or pulmonary embolism were used to ascertain the presence of VTE. Multivariable linear and logistic models were developed to evaluate the independent association of VTE with outcomes of interest. Results: Of an estimated 537, 522 patients meeting inclusion criteria, .55% developed VTE during index hospitalization (.14%) or within 90 days of index discharge (.41%). Compared to others, VTE patients were older (51.8 vs 44.9 years, P <.001), more commonly male (20.0% vs 31.5%, P <.001), and had gastric bypass (56.3% vs 31.9%, P <.001) or an open procedure (21.9% vs 2.6%, P <.001). After risk adjustment, several factors including increasing age, male gender, gastric bypass and open approach remained associated with increased odds of VTE. Patients with VTE during index hospitalization had greater odds of mortality (AOR 11.6, 95% CI: 6.12-22.19) and increased index LOS (β:+14.1 days, 95% CI: 11.7-16.5) and hospitalization costs (β: +$53, 100, 95% CI: 43, 100-63, 500). Additionally, VTE patients had greater odds of readmission within 90 days (AOR 1.86, 95% CI: 1.40-2.47). Conclusions: Although VTE is uncommon following bariatric operations, it is significantly associated with increased mortality, readmission, and resource use. Further research is necessary to ascertain optimal management of VTE for bariatric surgery patients.